AN OVERVIEW OF CELIAC DISEASE IN CHILDHOOD TYPE 1 DIABETES - A SINGLE CENTER EXPERIENCE FROM SOUTH EAST ROMANIA - Tatiana Chisnoiu; Cristina Maria Mihai; Alexandru Cosmin Pantazi; Adriana Luminița Balasa; Larisia Mihai; Corina Elena Frecus; Bianca Maria Constantin; Antonio Andrusca; Ancuta Lupu; Iuliana Magdalena Starcea; Ileana Ioniuc; Lorenza Forna; et al. (Romanian Society of Oral Rehabilitation, 2024)
The autoimmune process that induces type 1 diabetes can also affect other organs, leading to the development of additional autoimmune diseases in patients, thus hindering diabetes control. The most common comorbidities include autoimmune thyroid diseases and celiac disease. Globally, this subject is increasingly drawing the attention of researchers, given the magnitude and severity of the association between autoimmune diseases and type 1 diabetes. The aim of the present study is to assess the prevalence of autoimmune diseases, with the primary focus on celiac disease, associated with type 1 diabetes in children and adolescents, as well as their impact on the progression of type 1 diabetes. Material and methods: The present study was conducted within the Pediatric Section, Pediatric Diabetology Department of the Emergency Clinical Hospital "St. Apostle Andrew" in Constanța, including 15 cases diagnosed with type 1 diabetes in children during the period 2017-2022. Results: The patients included in the study are aged between 1 and 13 years highlighting the age group of 3-6 years as the most commonly encountered. The most commonly encountered HbA1c values are in the range of 10-12%, accounting for 53% of the total, we can thus observe a prevalence of high and very high HbA1c values. In order to confirm the diagnosis of type 1 diabetes, specific antibodies were sampled, 97% of patients being tested positive for at least one antibody. Conclusions: The association between diabetes mellitus and another autoimmune disease is encountered at a relatively high percentage. Higher levels of HbA1c at the onset of type 1 diabetes have been associated with an increased risk of long-term complications.